PLN: The paradigm shift in teacher and learner autonomy - Stevens, Vance (2010)
This presentation explains a dozen tools and paradigm shifts that teachers should apply in transformative ways to working with their students, how Web 2.0, tagging, and RSS are crucial to this process, and how teachers can develop their own personal learning networks to practice continuous lifelong learning and 'teacher autonomy' before applying these concepts to students.